Cost-efficiency analyses for the US of biosimilar filgrastim-sndz, reference filgrastim, pegfilgrastim, and pegfilgrastim with on-body injector in the prophylaxis of chemotherapy-induced (febrile) neutropenia. (3rd October 2017) - McBride, Ali; Campbell, Kim; Bikkina, Mohan; MacDonald, Karen; Abraham, Ivo; Balu, Sanjeev
Abstract: Aims: Guidelines recommend prophylaxis with granulocyte colony-stimulating factor for chemotherapy-induced (febrile) neutropenia (CIN/FN) based on regimen myelotoxicity and patient-related risk factors. The aim was to conduct a cost-efficiency analysis for the US of the direct acquisition and administration costs of the recently approved biosimilar filgrastim-sndz (Zarxio EP2006) with reference to filgrastim (Neupogen), pegfilgrastim (Neulasta), and a pegfilgrastim injection device (Neulasta Onpro; hereafter pegfilgrastim-injector) for CIN/FN prophylaxis. Methods: A cost-efficiency analysis of the prophylaxis of one patient during one chemotherapy cycle under 1–14 days' time horizon was conducted using the unit dose average selling price (ASP) and Current Procedural Terminology (CPT) codes for subcutaneous prophylactic injection under four scenarios: cost of medication only (COSTMED), patient self-administration (SELFADMIN), healthcare provider (HCP) initiating administration followed by self-administration (HCPSTART), and HCP providing full administration (HCPALL). Two case studies were created to illustrate real-world clinical implications. The analyses were replicated using wholesale acquisition cost (WAC). Results: Using ASP + CPT, cost savings achieved with filgrastim-sndz relative to reference filgrastim ranged from $65 (1 day) to $916 (14 days) across all scenarios. Relative to pegfilgrastim, savings with filgrastim-sndz ranged from $834 (14 days) up to $3, 666 (1 day) under the COSTMED, SELFADMIN, and HPOSTART scenarios; and from $284 (14 days) up to $3, 666 (1 day) under the HPOALL scenario. Similar to the cost-savings compared to pegfilgrastim, filgrastim-sndz achieved savings relative to pegfilgrastim-injector: from $834 (14 days) to $3, 666 (1 day) under the COSTMED scenario, from $859 (14 days) to $3, 692 (1 day) under SELFADMIN, from $817 (14 days) to $3, 649 (1 day) under HPOSTART, and from $267 (14 days) to $3, 649 (1 day) under HPOALL. Cost savings of filgrastim-sndz using WAC + CPT were even greater under all scenarios. Conclusions: Prophylaxis with filgrastim-sndz, a biosimilar filgrastim, was associated consistently with significant cost-savings over prophylaxis with reference filgrastim, pegfilgrastim, and pegfilgrastim-injector, and this across various administration scenarios.